Internalizing the Values of the PNO Adat Kerinci as a Source of Social Studies Learning - Asnimawati, Asnimawati; Supriatna, Nana; Saripudin, Didin; Ruhimat, Mamat (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This article aims to provide an overview of the results of research on the internalization of local wisdom values of the Kerinci community as a source of social studies learning in junior high schools. The method used is ethnography and action research. The results show that in the Kerinci Pno Adat there are 1) the Kerinci Pno adat contains the meaning of character education values which are used as guidelines for behavior by the community, 2) The values in the adat pno include religious values, social care and environmental care, 3) values in Pno adat can be used as a source of social studies learning. The important meaning contained in each traditional pno expression is very important to make social studies learning more meaningful. The importance of values in the Kerinci Pno Adat can be seen in two important things to students. First, the students' interest and passion for learning has increased. Second, teachers and books are no longer the main source of learning.